2016
DOI: 10.5352/jls.2016.26.6.663
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effects and Cell Cycle Arrest Effects of Extracts from Cnidium monnieri (L.) Cusson through Regulating Akt/mTOR/GSK-3β Signaling Pathways in HCT116 Colon Cancer Cells

Abstract: The Cnidium monnieri (L.) Cusson is an annual plant distributed in China and Korea. The fruit of C. monnieri is used as a medicinal herb that is effective for the treatment of carbuncle and pain in female genitalia. However, the anti-cancer effects of CME have not yet been reported. In this study, we assessed the apoptotic effects and cell cycle arrest effects of ethanol extracts from C. monnieri on HCT116 colon cancer cells. The results of an MTT assay and LDH assay demonstrated a decrease in cell viability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…1(d). These results indicated that CME treatment induces anti-proliferative, cytotoxic, and cell morphological changes in HT-29 colon cancer cells also like other studies [26][27][35][36][37][38]. Western blot analysis of Bcl-2, Bak, Cytochrome c, COX-IV, and β-actin in cytosolic and mitochondrial fractions of HT-29 cells treated with CME (40~80 μg/mL) for 24 h. The β-actin probe served as protein-loading control in cytosol.…”
Section: Cme Treatment Inhibits Cell Proliferation and Induces Morpho...supporting
confidence: 88%
See 2 more Smart Citations
“…1(d). These results indicated that CME treatment induces anti-proliferative, cytotoxic, and cell morphological changes in HT-29 colon cancer cells also like other studies [26][27][35][36][37][38]. Western blot analysis of Bcl-2, Bak, Cytochrome c, COX-IV, and β-actin in cytosolic and mitochondrial fractions of HT-29 cells treated with CME (40~80 μg/mL) for 24 h. The β-actin probe served as protein-loading control in cytosol.…”
Section: Cme Treatment Inhibits Cell Proliferation and Induces Morpho...supporting
confidence: 88%
“…Many previous studies reported that natural plant extracts suppress cell proliferation in colon cancer cells [35][36][37][38]. Moreover, the treatments of CME did not show cytotoxicity in normal cells such as Fibroblast and HaCaT cells [26,27]. We examined the anti-proliferative and cytotoxic effects of CME using the MTT assay and LDH release assay.…”
Section: Cme Treatment Inhibits Cell Proliferation and Induces Morpho...mentioning
confidence: 99%
See 1 more Smart Citation